BARRIER OPTION - Yovita Vivianty Indridewi Atmadjaja (Bina Ekonomi, 2000)
Barrier options are the popular form of exotic options. Exotic options refer to non-standard option, which emerge due to the development in financial and option technology, the increased focus on risk management and the increased focus on the inadequacies of existing risk-management tools. Barrier options are becoming more common in the over the counter markets as alternative hedging tools since they provide cheaper price than plain European options. Barrier option is non-standard option because it has more complicated payoffs than the standard European and American option and has different activation or expiration mechanism with standard option.